2021
DOI: 10.14814/phy2.14873
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of respiratory effort with EMG extracted from ECG recordings during prolonged breath holds: Insights into obstructive apnea and extreme physiology

Abstract: Extended breath holds by divers experienced with commercial (sustenance diving, e.g., the Ama divers of Japan), recreational (e.g., spear fishing, videography), or competitive (static, dynamic, and depth disciplines) apneic activities have shed important light on cardiorespiratory physiology. The breath hold, which can last many minutes, is comprised of an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…A schematic representation of the BH maneuver with its tasks, phases, and durations is given in Figure 1 (spontaneous breathing time frames were established based on [ 23 , 31 ]). Breath holding began after spontaneous exhalation to functional residual capacity (FRC), with the suggestion of refraining from preparatory hyperventilation, and ended with spontaneous inhalation.…”
Section: Databasementioning
confidence: 99%
See 1 more Smart Citation
“…A schematic representation of the BH maneuver with its tasks, phases, and durations is given in Figure 1 (spontaneous breathing time frames were established based on [ 23 , 31 ]). Breath holding began after spontaneous exhalation to functional residual capacity (FRC), with the suggestion of refraining from preparatory hyperventilation, and ended with spontaneous inhalation.…”
Section: Databasementioning
confidence: 99%
“…OSAHS leads to sleep fragmentation and intermittent hypoxia during sleep, while, in the long term, it has also been reported to be part of age-related diseases and to accelerate aging mechanisms [ 19 ], as well as other disorders and diseases [ 20 , 21 ]. OSAHS is still an underdiagnosed condition, but recent studies have not only shown that OSA can be identified using simple breath-holding maneuvers performed during wakefulness [ 22 ], but some research approaches suggest that it can be modeled using prolonged breath-holding [ 23 ], which highlights the importance of the reliable identification and characterization of IBMs.…”
Section: Introductionmentioning
confidence: 99%